The effect of tooth brushing counseling on increasing knowledge of dental and oral health of physical education teachers - Haryani, Wiworo; Putri, Shanti Yolanda; Widayati, Aryani (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Dental and oral health requires comprehensive handling. Prevention of dental and oral diseases can be done by providing dental health education from an early age, counseling is very effective in improving the level of dental and oral health. Purpose: To determine the effect of brushing counseling on dental and oral health knowledge of elementary physical education teachers in Padang Panjang. Methods: This type of research is a quasi-experimental research with a total sampling technique with a total population of 42 physical education teachers, 21 people are included in the experimental group, namely the group that is given counseling and 21 others are included in the control group, namely the group that is given counseling using leaflet media. This study uses the Wilcoxon Signed Ranks Test hypothesis test. Results: The level of knowledge of dental and oral health before counseling was 33.3% in good criteria, 47.6% enough and 19.0% less and after counseling it became a good category that is, 90.5%, enough 9.5% and less as much as 0 %. The Wilcoxon Signed Ranks Test results showed significant value of 0.000 and 0.000 <0.05. Conclusion: Counseling teeth brushing an effects on increasing knowledge of oral and dental health on physical education teachers